SAT0125 Utility of Select Plasma Mirnas for Diagnosis of Rheumatoid Arthritis and Monitoring of Disease Activity and Cardiovascular Risk. (9th June 2015) - Ormseth, M.; Solus, J.; Vickers, K.; Oeser, A.; Raggi, P.; Stein, C.M.
Abstract : Background: MicroRNAs (miRNAs) are short RNA sequences that are gene expression regulators and potential mediators and markers of disease. Recently, plasma miR-24-3p and miR-125a-5p concentrations were shown to be elevated in rheumatoid arthritis (RA) and useful for RA diagnosis. We assessed the utility of seven candidate plasma miRNAs, selected for biologic plausibility, for diagnosis of RA and use as markers of disease activity and cardiovascular risk in RA. Methods: The cross-sectional study included 168 patients with RA and 91 controls, of similar age, race and sex. Plasma concentrations of miR-15a-5p, 24-3p, miR-26a-5p, miR-125a-5p, miR-146a-5p, miR-155-5p, and miR-223-3p were measured by quantitative PCR. Utility of plasma miRNA concentrations for diagnosis of RA was assessed by area under the receiver operating characteristic curve (AUROC). Association between plasma miRNA concentrations and RA disease activity and cardiovascular risk measures were assessed by Spearman correlations. Results: Plasma concentrations of miR-15a-5p, 24-3p, miR-26a-5p, miR-125a-5p, miR-146a-5p, miR-155-5p, and miR-223-3p were significantly increased in patients with RA. miR-24-3p had the highest AUROC for diagnosis of RA (AUROC=0.725), including among rheumatoid factor negative patients (AUROC=0.772). Among all patients with RA, the combination of miR-24-3p, miR-26a-5p and miR-125a-5p improved the model modestly (AUROC=0.737). miR-155-5p was weakly inversely associated with swollen joint count (P=0.024), but no other miRNAs were associated with disease activity or coronary artery calcium score. Conclusions: The combination of miR-24-3p, miR-26a-5p and miR-125a-5p had strongest diagnostic accuracy for RA. Candidate miRNAs had minimal or no association with RA disease activity and coronary calcium score. Disclosure of Interest: None declared